The Nexus of Governance, Branding, and Tourist Behavior in Shaping Solo City's Halal Tourism - Kurniawati Darmaningrum; Rini Adiyani; Sri Wijiastuti; Supartini Supartini; Istinganah Eni Maryanti; Syahriar Abdullah; Retnoning Ambarwati; Dhea Sashinta Ashari (Journal of Economics Education and Entrepreneurship, 2026)
Halal tourism is a rapidly growing segment of the global travel industry, presenting both opportunities and challenges for destinations targeting Muslim travelers. Solo City holds strong potential to become one of Indonesia’s leading halal tourism destinations due to its rich Islamic heritage and multicultural environment. This study integrates collaborative governance, destination branding, and tourist behavior theories, considering the moderating role of sociocultural context and the facilitating effect of policy support. Using data from 463 respondents, including tourists, MSMEs, policymakers, and community leaders, analysis was conducted through Structural Equation Modeling (SEM) with AMOS. Findings reveal that visitor behavior, destination branding, and cooperative governance significantly influence the growth of halal tourism in Solo City, with visitor behavior emerging as the strongest predictor, emphasizing service experience, satisfaction, and loyalty. Sociocultural context negatively moderates the impact of branding but positively moderates governance effects, reflecting tensions between local identity and top-down branding. Policy support enhances the influence of both branding and governance through incentives, certification, and regulation. The study concludes that Solo City’s halal tourism development should emphasize stakeholder collaboration, authentic branding, tourist-centered services, culturally sensitive strategies, and supportive policies. Theoretically, this research integrates multiple perspectives in halal tourism studies and provides practical insights for policymakers and tourism stakeholders to strengthen Solo City’s competitiveness in the halal tourism market.